Efficacy of Schisandra chinensis in liver injury: a systematic review and preclinical meta-analysis - Huang, Bo-Hao; Lv, Bo-Han; Wu, Dong-Jie; Xiong, Fei-Yang; Li, Yan-Bo; Lu, Yan-Ping; Lv, Wen-Liang (Frontiers in Pharmacology, 2025)
BackgroundLiver injury is a multifaceted condition marked by oxidative stress, inflammation, and apoptosis. Schisandra chinensis, a traditional Chinese medicinal herb with a history of use spanning over 2,000 years, exhibits significant hepatoprotective, antioxidant, anti-inflammatory, and anti-apoptotic effects. This study aims to review the therapeutic effects and underlying mechanisms of Schisandra chinensis in mitigating liver injury in animal models.MethodsA systematic review was conducted across eight databases. The methodological quality of the studies was assessed using the Sycle’s RoB tool. Sensitivity and subgroup analyses were performed in cases of high heterogeneity. Publication bias was evaluated using Egger’s test and funnel plots. A meta-analysis was carried out using Stata 18.0.ResultsA total of 54 animal studies were included in this review. The results indicated that bioactive compounds in Schisandra chinensis significantly reduced levels of alanine aminotransferase (ALT) [standardized mean difference = −4.74, 95% confidence interval (−5.42, −4.06), p < 0.001, I2 = 90.8%], aspartate aminotransferase (AST) [SMD = −5.10, 95% CI (−5.84, −4.37), p < 0.001, I2 = 91.7%], and alkaline phosphatase (ALP). Additionally, Schisandra chinensis decreased malondialdehyde (MDA) levels while increasing superoxide dismutase (SOD) and glutathione (GSH). Additionally, the results revealed a significant reduction in pro-inflammatory cytokines, including Tumor Necrosis Factor-alpha (TNF-α), Interleukin-6 (IL-6), and Interleukin-1 beta (IL-1β). Subgroup analysis suggested that variations in animal species, drugs, modeling methods, and dosages may contribute to the observed heterogeneity.ConclusionSchisandra chinensis demonstrates significant therapeutic effects in liver injury, likely due to its anti-inflammatory, antioxidant, and anti-apoptotic properties. However, further research is needed to validate its efficacy and safety.Systematic Review Registrationhttps://inplasy.com/inplasy-2025-2-0084/, identifier INPLASY202520084.